The formulation of emulsions in biodiesel production : emulsion stability and demulsification via micromave heating - Faradila, Rozali (2008)
In production of biodiesel, emulsions resulted from washing process is important as a method to remove sediment contaminant or by-product. Ironically, there have been a few cases when oil becomes a stable emulsion during water washing process. These situations normally cause by an aggressive washing biodiesel in the presence of soap and water. Formation of these emulsions is costly, due to chemical used and production losses. Therefore, the aim of this study is to understand the stability of emulsions and to investigate the effectiveness of using microwave radiation to break the stable emulsions. In order to accomplish the objectives of the study, emulsions were prepared in a lab with water and biodiesel as raw materials. Part 1 of experiment was investigated the formation and stabilizations of emulsions by using two different emulsifying agent; Sodium Dodecyl Sulfate and Triton X100. Concentration of emulsifier varied between 1.5% to 3% total volume while water-to-oil ratio was varied from 30-50:70-50. The stability studies were carried out by analyzes the viscosity using viscometer and visually observes on separation layer. As a result, an existence correlation between the effect of using different emulsifying agent, the emulsifiers concentration, and water-oil ratio with emulsion stability were discovered. In term of demulsification study via microwave radiation, it has been found that the effect of microwave power is proportional to the separation efficiency of emulsions. Demulsification by using microwave is primarily due to heat temperature; therefore as the rate power output of microwave oven is increase, the temperature will increase and this lead to fast separation of water from emulsions. Microwave has features of penetrating power; in which can distributes its energy within the bulk of materials thus suspends water droplets in an emulsion.-Author